Penggunaan Media Big Book Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I di SDN Percobaan Palangka Raya: The Use of Big Book Media to Improve Reading Ability for Beginners of First Grade Students at SDN Percobaan Palangka Raya - Novelia Kristina; Netto W.S. Rahan (Pusat Kajian Bahasa Daerah & Budaya, 2023)
This study aims to improve initial reading skills through Big Book media in class I students of Experimental Elementary School in Palangka Raya, Central Kalimantan Province. This type of research is collaborative classroom action research. This research model uses the Kemmis and Mc Taggart models. The subjects of this study were class I A students consisting of 26 students. Data collection techniques in this study used observation, tests and documentation. Qualitative data collection instruments used observation sheets and quantitatively used reading ability tests. The data analysis technique used is quantitative and qualitative descriptive data analysis. This study shows that the use of Big Book media can improve the initial reading ability of class I A students. The increase in initial reading ability is evidenced by the class average score of the pre-action 53.8 cycle I 69.0, and cycle II 80.0. The percentage of achieving an average score in reading ability increased in the pre-action by 23%, the first cycle was 69%, and the second cycle was 93%. This shows that from cycles I to II, the average reading ability of students has increased and it can be concluded that the application of Big Book media can improve students' reading abilities.